THU0261 Cardiovascular risk stratification in ankylosing spondylitis: lateral lumbar radiography is useful to detect high-cardiovascular risk patients. (12th June 2018) - Martín-Varillas, J.L.; Atienza-Mateo, B.; Vegas-Revenga, N.; Dominguez-Casas, L.; Rueda-Gotor, J.; Genre, F.; Corrales, A.; Blanco, R.; Fuentevilla, P.; Portilla, V.; Expósito, R.; Mata, C.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is associated with increased rates of cardiovascular (CV) disease. CV events in these patients can be prevented by identifying patients at high risk who can benefit from appropriate primary prevention measures. The systematic coronary risk evaluation (SCORE) is the predictive model recommended in Europe, but it underestimates the CV risk in AS. Objectives: To determine if a lateral lumbar radiography, which is available in most of AS patients, may help to identify AS patients at high risk of CV disease. Methods: 125 AS patients older than 35 years old without history of CV events, diabetes mellitus or chronic kidney disease were recruited. All patients underwent a carotid ultrasound (US) and lateral lumbar spine radiography and a multi-detector coronary tomography (MDCT) was also performed in a subgroup of 43 AS patients. Carotid plaques were defined according to the Mannheim consensus and the presence of AAC as calcific densities visible in an area parallel to the lumbar spine and anterior to the lower part of the spine. A Coronary Artery Calcification Score (CACS) superior to 100 were considered as a surrogate marker of coronary atherosclerosis. CV risk was calculated according to the total cholesterol systematic coronary risk evaluation (TC-SCORE). Results: CV risk was categorised according to the TC-SCORE as low (<1%; n=64), moderate (≥1% and <5%; n=54) and high/very high risk (≥5%; n=7). Most patients with low TC-SCORE did not show CAA, which was only present in 3 patients (4, 68%). In contrast, 38, 9% of patients included in the moderate-risk group had CAA. The lateral lumbar radiography showed a sensitivity to detect subclinical atherosclerosis lower than that observed by carotid US, which found plaques in 61% of patients with moderate TC-SCORE, but superior to the MDCT (61, 9% Vs 28, 6% in the subgroup of 43 patients). 89% of patients with AAC also had carotid plaques (r=0.49, p<0, 0001). We set up a predictive model to disclose the largest number of AS with high/very high CV risk, defined by the presence of carotid plaques or a TC-SCORE ≥5% (table 1 ). A model including patients with a chart TC-SCORE ≥5% along with the presence of AAC showed a sensitivity of 50, 9% (model 4). The combination of a TC-SCORE ≥5% and the performance of carotid US in patients with a moderate SCORE showed the highest sensitivity to detect patients at high/very high risk (72, 7%, model 2). Nevertheless, model 4 showed greater specificity than model 2 (70% Vs 95.7%), leading to a higher global diagnostic accuracy (area under curve: 0, 73 Vs 0, 71). Conclusions: Several AS patients at high CV risk who are underdiagnosed as having very high CV risk by the SCORE can be detected by a lateral lumbar radiography. Disclosure of Interest: None declared